Head teachers’ leadership practices and teachers’ motivation: teachers’ perspective. - Frey, Cassandra (2016)
To be motivated for work, and to keep that motivation over time, is for all professions a challenge. Drawing upon findings of narratives of 10 primary and secondary school teachers with different years of experience and coming from six different countries, this work provides empirical evidence about which factors are motivating teachers for their work, how does teachers’ motivation evolve during their career, and how school leaders’ leadership practices influence teachers’ motivation. Findings show three different types of motivation to enhance a teaching career: altruistic, intrinsic and extrinsic motivations. Most of the teachers are motivated to teach for altruistic or intrinsic reasons, with the desire to ameliorate children’s lives, to realise their dreams, or to have continual intellectual stimulation. This research also demonstrates that teachers’ having altruistic or intrinsic motivations to do their job have a higher commitment rate than those working for extrinsic motives. As teachers’ motivation evolves over time, the research divided teachers’ careers into three stages in order to understand the difficulties that teachers’ meet in each phase, and consequently help them sustaining their motivation. As it has been found that leaders have an influence on teachers’ motivation and effectiveness, having an effective leader helps teachers feeling well with their profession. Consequently according to all participants the school leader should be present in the school and support his teachers.